COMMENTS ON THE DEFINITION OF EARNED SURPLUS. - Heckert, J. B. (The Accounting Review, 1930)
Abstract On September 10, 1929, the special committee of the American Institute of Accountants on definition of earned surplus submitted its report to the Council of the Institute. This report was subsequently sent to all members and associates of the Institute and given somewhat general publicity. Earned surplus is the balance of net profits, income and gains of a corporation from the date of incorporation after deducting losses and after deducting distributions to stockholders and transfers to capital stock accounts when made out of such surplus. Surplus in its broadest sense is the amount of the stockholders' equity in a corporation in excess of that represented by capital-stock accounts. Capital surplus comprises paid-in surplus, donated surplus and revaluation surplus-that is, surplus other than earned surplus. Profits arising from the sale or other disposition of fixed assets or from the resale of the corporation's own capital stock are properly included in earned surplus. Earned surplus is not properly consolidated with capital-stock accounts on the balance-sheet without specific corporate action authorizing such procedure.